Investigating hybrid methods of fabricating formamidinium-based perovskite solar cells - Krishnan, Sriniketh (Nanyang Technological University, 2024)
Given mankind’s increasing demand for energy coupled with the challenges posed by climate change, renewable energy technologies have become the need of the hour, with solar energy leading the charge. While most solar cells today are polycrystalline silicon-based, they are heavy, rigid, and have a theoretically limited efficiency. Hence, a global effort into emerging technologies like perovskite solar cells (PSCs) is being undertaken. Although solution processing is the most popular and successful method to fabricate perovskites, it is limited by its scalability and use of toxic solvents. In this regard, fully thermally evaporated PSCs or a two-step hybrid are ideal alternatives, with uniform deposition, conformal coverage, and excellent process control. Even though thermally evaporated methylammonium-based (MA) PSCs have achieved efficiencies of over 20%, the composition and bandgap tuning are still complex, while being less stable than formamidinium-based (FA) PSCs. Thus, this project explored the industry-favored perovskite deposition process to fabricate scalable, highly efficient, and phase-stable FA-based perovskite solar cells, suitable for tandem integration with silicon bottom cells. A double-step method was explored on a p-i-n structure, consisting of thermal evaporation of an inorganic layer (PbI2 or PbI2-Cs) followed by spin coating of an organic layer (CH(NH)2I/CH3NH3Br/CH3NH3Cl) to complete the perovskite. The thickness, temperature, deposition rate, and morphology of the first inorganic step were optimized, followed by device fabrication through varying solution concentrations, post-annealing temperatures, and spin coating parameters. The PSCs fabricated using the PbI2 inorganic template suffered from phase instability, indicated by color change after ambient exposure. To provide greater structural stability to the black FA-based perovskite, Cs was added as the A-site cation in the thermal evaporation stage. The devices were found to be reproducible with a champion efficiency of 10.68% for the Pb-template devices and 17.09% for the PbI2/Cs-template devices. This paper details the fabrication process of these perovskites, their characterization, their advantages, and associated challenges.